PFISR observation of intense ion upflow fluxes associated with an SED during the 1 June 2013 geomagnetic storm. Issue 2 (24th February 2017) - Zou, Shasha; Ridley, Aaron; Jia, Xianzhe; Boyd, Emma; Nicolls, Michael; Coster, Anthea; Thomas, Evan; Ruohoniemi, J. M.
Abstract: The Earth's ionosphere plays an important role in supplying plasma into the magnetosphere through ion upflow/outflow, particularly during periods of strong solar wind driving. An intense ion upflow flux event during the 1 June 2013 storm has been studied using observations from multiple instruments. When the open‐closed field line boundary (OCB) moved into the Poker Flat incoherent scatter radar (PFISR) field of view, divergent ion fluxes were observed by PFISR with intense upflow fluxes reaching ~1.9 × 10 14  m −2  s −1 at ~600 km altitude. Both ion and electron temperatures increased significantly within the ion upflow, and thus, this event has been classified as a type 2 upflow. We discuss factors contributing to the high electron density and intense ion upflow fluxes, including plasma temperature effect and preconditioning by storm‐enhanced density (SED). Our analysis shows that the significantly enhanced electron temperature due to soft electron precipitation in the cusp can reduce the dissociative recombination rate of molecular ions above ~400 km and contributed to the density increase. In addition, this intense ion upflow flux event is preconditioned by the lifted F region ionosphere due to northwestward convection flows in the SED plume. During this event, the OCB and cusp were detected by DMSP between 15 and 16 magnetic local times, unusually duskward. Results from a global magnetohydrodynamics simulation using the Space Weather Modeling Framework have been used to provide a global context for this event. This case study provides a more comprehensive mechanism for the generation of intense ion upflow fluxes observed in association with SEDs. Key Points: A more comprehensive mechanism for the generation of intense ion upflow fluxes observed in association with SEDs has been provided Northwestward convection flows lift the F region ionosphere within SED and provide seed population for intense ion upflow fluxes Significantly elevated electron temperature reduces recombination rate contributing to density increase